Saints and spectacle : Byzantine mosaics in their cultural setting - Connor, Carolyn L. (Oxford scholarship online, 2016)
The awe-inspiring mosaics covering the walls, vaults, and domes of Byzantine churches of the medieval period still remain a mystery to modern viewers. Saints and Spectacle ventures into the world of ninth- and tenth-century Constantinople, the capital of the Byzantine Empire, to recapture the spirit of Byzantine thought and expression after Iconoclasm. Texts, artworks, and the archaeological record aid in reconstructing the visual and literary context of the age of the first rulers of the Macedonian Dynasty